Analisis Strategi Pengembangan Usaha pada Orlin Beauty Skincare Brebes dalam Meningkatkan Daya Saing di Industri Kecantikan - Agus Susilo; Ary Kusmanto (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2026)
The beauty industry is one of the fastest-growing business sectors in Indonesia. This situation encourages businesses to develop appropriate business development strategies to remain competitive. This study aims to analyze the business development strategies implemented by Orlin Beauty Skincare Brebes to increase competitiveness in the beauty industry. The study employed qualitative methods, with data collection techniques including observation, interviews, documentation, and literature review. Data analysis employed a SWOT approach to identify the company's strengths, weaknesses, opportunities, and threats. The results indicate that the strategies implemented include product development, improving service quality, and utilizing digital marketing. The company's primary strengths lie in personalized service and customer loyalty, while its weaknesses are limited capital and market reach. Opportunities stem from increasing public awareness of skincare, while threats stem from intense industry competition. Service differentiation strategies and strengthening digital marketing are key strategies for increasing the company's competitiveness in both local and regional consumer markets.